Between stigma and mother‐blame: blind mothers' experiences in USA hospital postnatal care. Issue 8 (30th April 2015) - Frederick, Angela
Abstract: This study examines instances of discrimination that blind mothers in the USA have experienced at the hands of doctors, nurses and social workers during hospital postnatal care. The author identifies postnatal care as the time when blind mothers are likely to face the most stigmatising interactions with medical staff, as it is when scepticism about their competence as mothers is at its height. The author argues these interactions must be understood within their institutional context in which ideologies of risk and mother‐blame are embedded in hospital postnatal practices.